Preparation And Characterization Of Xylo-Oligosaccharides From Oil Palm Frond (Elaeis Guineensis) - Hussin, Farah Salina (2011)

(untitled)
This study focused on factors relevant for enzymatic hydrolysis of lignocellulosic raw materials derived from oil palm frond (OPF). Two origins of xylanase enzyme were used ; Trichoderma viride (T.viride xylanase) and Thermomyces lanuginosus (T.lanuginosus xylanase) at its own optimum pH 5.5 and pH 6.5. The major interest of this work is the isolation of xylo-oligosaccharides (XOS) from delignified hemicellulose by using enzymatic hydrolysis method. Delignification of OPF was done by alkaline peroxide treatment at 80 oC and the extraction of hemicellulose by using alkaline extraction method.